VILLAGE FUND MANAGEMENT IN AN EFFORT TO IMPROVE COMMUNITY DEVELOPMENT AND EMPOWERMENT - Sony Setyawan; Hepiana Patmarina (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This research aims to determine the management of village funds as an effort to improve the development and empowerment of the Wates Village community in 2023. It is hoped that the results of this study will be an important guide in understanding the best way to manage Village Funds to improve community development and empowerment in Wates Village. This research is qualitative research that uses a descriptive approach. Village Head, Village Secretary, Head of Finance, Head of Community  Welfare, and Community Leaders are selected informants. The author collected data through interviews and direct observations one’s financial management. Data collection techniques include collecting, reducing, conveying, and drawing conclusions. That Permendagri No. 20 of 2018 concerning village financial management has been complied with in terms of planning, implementation, administration, reporting, and accountability. In Wates Village, the physical development program and its implementation have been going well. However, the funds allocated for community empowerment have been reduced, so people who generate income from MSME products are not given entrepreneurship training. As a result, community empowerment programs in 2023 did not achieve the expected level of success. However, the necessary infrastructure development is prioritized in the Wates Village government's development plan and is carried out in a self-managed manner through the desal cash intensive system (PKTD). Thus, income and economic resilience will increase.